Opioids, sleep, analgesia and respiratory depression: Their convergence on Mu (μ)-opioid receptors in the parabrachial area - Lynch, Nicole; Lima, Janayna D.; Spinieli, Richard L.; Kaur, Satvinder (Frontiers in Neuroscience, 2023)
Opioids provide analgesia, as well as modulate sleep and respiration, all by possibly acting on the µ-opioid receptors (MOR). MOR’s are ubiquitously present throughout the brain, posing a challenge in understanding the precise anatomical substrates that mediate opioid induced respiratory depression (OIRD), which ultimately kills most users. Sleep is a major modulator not only of pain perception, but also of opioid efficacy as an analgesic. Therefore, sleep disturbances are major risk factors for developing opioid overuse, withdrawal symptoms, inadequate pain treatment, and addiction relapse. Despite challenges to resolve the neural substrates of respiratory malfunctions during opioid overdose, two main areas, the pre-Bӧtzinger complex (preBӧtC) in the medulla and the parabrachial (PB) complex have been implicated in regulating respiratory depression. More recent studies suggest that it is mediation by the PB that causes OIRD. The PB also act as a major node in the upper brain stem that not only receives input from the chemosensory areas in medulla, but also receives nociceptive information from spinal cord. We have previously shown that the PB neurons play an important role in mediating arousal from sleep in response to hypercapnia through its projections to the forebrain arousal centers, and it may also act as a major relay for the pain stimuli. However, due to heterogeneity of cells in the PB, their precise roles in regulating, sleep, analgesia, and respiratory depression, needs to be addressed. This review sheds light on the interactions between sleep and pain, and dissects the elements that adversely affects respiration.